The Influence of Public Relations, Facilities, and Service Quality on Student Enrollment Decisions - Ike Dian Sri Lestari; Moh Bukhori; Widi Dewi Ruspitasari (Al-Qalam Institue, 2023)
The following research explores the influence of curriculum variables and school reputation on students' decisions in choosing secondary schools. This study aims to determine the effect of Public Relations, Facilities, and Service Quality on the Decision to Register at SMK Muhammadiyah 2 Probolinggo City. This research is quantitative and descriptive. The population of this study were students of class X, XI, and class XII at SMK Muhammadiyah 2 Probolinggo City, totaling 64 students. The sample used in this study included all class X, XI, and XII students with all majors in light vehicle engineering (TKR) and multimedia (MM). Data collection techniques in this study were questionnaires, observation, and documentation. The analysis technique used is Multiple Linear Regression analysis, and this research uses the SPSS 26 statistical analysis tool. The results show that public relations positively and significantly affect school enrollment decisions. School facilities have a positive and significant effect on school enrollment decisions. Moreover, the quality of service has a positive and significant effect on the decision to enroll in school. The implications of this research are the critical role of Public Relations, facilities, and service quality in attracting students' interest in enrolling in school, as well as the need for more attention to these aspects in school management to increase the competitiveness and image of educational institutions.